Research methods : the basics - Walliman, Nicholas (The basics, 2022)
"Research Methods: The Basics is an accessible, user-friendly introduction to the different aspects of research theory, methods and practice. This third edition provides an expanded and fully updated resource suitable for students and practitioners in a wide range of disciplines including the natural sciences, social sciences and humanities. It is structured in two parts - the first covers the nature of knowledge and the reasons for doing research, the second explains the specific methods used to conduct an effective research project and how to propose, plan, carry out and write up a research project. This book covers: Reasons for doing a research project ; Structuring and planning a research project ; The ethical issues involved in research ; Different types of data and how they are measured ; Collecting primary and secondary data ; Analysing qualitative and quantitative data ; Mixed methods and interdisciplinary research ; Devising a research proposal and writing up the research ; Motivation and quality of work. Complete with student learning tasks at the end of each section, a glossary of key terms and guides to further reading, Research Methods: The Basics is the essential text for anyone coming to research for the first time"--